Automated Computation of the Instantaneous Velocity Centers of Planar Linkages (Determinación Automatizada de los Centros Instantáneos de Velocidad de Mecanismos Planos) - Srivastava, Sidharth; Corona Silva, Dario Isidro; García Castro, Oscar Daniel; Medel Varela, Ángel Ernesto; Pérez Zamudio, Fernando Tomás; García García, Ricardo; Rico Martínez, José María (JÓVENES EN LA CIENCIA, 2021)
This document presents a summary of the activities carried out during the XXVI Science Summer (XXVI Verano de la Ciencia). Since the group had an international student, from India, whose native language is English, it was decided to submit at least some of the documents in English. The project included two related but different topics: The automated computation of the instantaneous velocity centers of planar determinate linkages, and the determination of the instantaneous velocity centers of two-degree of freedom planar linkages. Both topics are related to the topics included in reasonable courses on planar kinematics but are usually beyond the topics usually included in those courses. Furthermore, the topics are of enough current interest to produce results that can be published in international scholarly journals.